Designing price-contingent vegetable rotation schedules using agent-based simulation - Jing LI; Daniel Rodriguez; Hao-xiang WANG; Liu-san WU (Journal of Integrative Agriculture, 2018)
Chinese vegetable production cooperatives supply their members, mostly smallholder farmers, with a rotation schedule for the year. Since vegetable prices are not stable throughout the year, designing a rotation schedule that maximizes expected profits, distributes farmers' profits more equitably, maintains the diversity of produce in the market, and reduces the risk of pests and diseases, requires adaptive, price-contingent rotation schedules (here, called “self-adaptive adjustment”). This study uses an agent-based simulation (ABS) to design self-adaptive rotation schedules that deliver these aims. The self-adaptive adjustment strategy was more profitable for farmers when faced with price volatility, and more equitable as well. This work provides a decision-support tool for managers of Chinese vegetable production cooperatives to provide farmers with more profitable and equitable rotation schedules.